A Sanguinicolid Blood Fluke In Sea Bass (Lates Calcarifer Bloch) In Coastal Peninsular Malaysia - Herbert, Brett W (1992)

(untitled)
Cruoricola lates N . Gen . , N . Sp . from the blood vessels of cultured seabass (Lates calcarifer Bloch 1790 ) is described . It is a lanceolate sanguinico lid with a single column of submarginal , ventral spines ; extensive vitellarium ; and X-shaped intestine. The single , lobed testis extends laterally to the caeca. The cirrus lies dorsal to the spherical seminal vesicle . Auxiliary seminal vesicle present. The uterus is post - ovarian , partly situated between the lobe s o f the ovary ; midportion is thick . Cruoricola lates N . Gen . , N. Sp . is found in all sea bass over 15g weight in the type The adults of C. lates primarily inhabit the venous circulation of Lates calcarifer. Eggs were found in t he kidney , liver , ventricle of the heart and gills of all fish examined three months after stocking .